Perancangan Checking Fixture Sebagai Alat Inspeksi Komponen Underwing Tank Enclosure Pada Pesawat Fixed-Wing - Kusuma, Samuel Surya; Hendaryanto, Ignatius Aris; Prayoga, Benidiktus Tulung; Winarno, Agustinus (Jurnal Teknik Mesin Indonesia, 2025)
The underwing tank enclosure is a component of fixed-wing aircraft that was originally manufactured by a Spanish aerospace company, so all the tools and references were not available to the Indonesian aerospace company, one of which is the inspection process tool. This study aims to design a checking fixture to meet requirements and support the production process of the underwing tank enclosure component, ensuring efficient and compliant inspection processes for the Indonesian aerospace company. The research utilized CAD software to design the checking fixture and CAE software to analyze the structural strength of the main fixture frame using the Finite Element Method (FEM). The results include a checking fixture design employing checking pins to validate the dimensional contours of the underwing tank enclosure against specified geometric specifications. Structural strength analysis revealed a maximum Von Mises stress of 1,1119 MPa, a maximum deformation of 0,0074696 mm, and a minimum safety factor of 211,34, while the checking plate deformation analysis shows that the longitudinal checking plate component only experiences a maximum deformation of 0,0010525 mm, confirming that the main structural frame of the checking fixture and checking plate components are safe for use. Keywords: Design, Checking fixture, Inspection, FEM.